The Impact of Profitability, Firm Size, and Sales Growth Toward Tax Avoidance in Agriculture Sector Companies Listed on the Indonesia Stock Exchange - Tarigan, Louis Yosen Primsa; Giovanni, Cynthia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the effects of profitability, firm size, and sales growth on tax avoidance. The target population consists of companies in the agriculture sector that are listed on the Indonesia Stock Exchange during the years 2020 to 2022. Employing a purposive sampling technique, 14 companies were chosen, resulting in a total of 42 samples for analysis. The research data were subjected to descriptive statistics, classical assumptions, multiple linear regression, and hypothesis testing, all conducted using SPSS 26. The results indicate that both profitability and sales growth have a beneficial impact on tax avoidance, while firm size appears to negatively affect tax avoidance. This research is conducted using quantitative research design. The population for this study includes agriculture sector companies that have been listed on the Indonesia Stock Exchange website from 2020 to 2022.